Effect of molecular structure and concentration of styrene-butadiene polymer on upper service temperature rheological properties of modified binders. (20th July 2020) - Kumar, Yogesh; Singh, Sumit K.; Oberoi, Deepa; Kumar, Praveen; Mohanty, Paritosh; Ravindranath, Sham S.
Highlights: Asphalt binders modified using four different molecular structures SB polymers. All molecular structures SB polymers have similar styrene content (≈ 30%). SB polymer content and molecular structure strongly influence the PMBs properties. Branched SB PMBs showed superior upper service temperature performance properties. Branched SB PMBs perform excellently at low polymer content, thereby cost benefits. Abstract: The upper service temperature rheological properties of styrene-butadiene (SB) polymer modified binders (PMBs) were analyzed as a function of the molecular structure (linear triblock, high vinyl triblock, branched triblock, and linear diblock SB polymers) and concentration of the SB polymer (1–8 wt%). The results show that the properties of the PMBs are strongly influenced by SB content >2.5–3 wt%, due to the formation of an interconnected polymer network. For the three triblock SB polymers, merely increasing the SB content from 3 to 4 wt%, the softening point (SP) and elastic modulus (at 0.1 rad/s and 60 °C) of the PMBs desirably increases by 15–20 °C and 100–200 Pa, while phase angle (δ) decreases by 20-25°. The molecular structure of the SB polymer also significantly influences the upper service temperature properties of the PMBs. Compared to linear SB PMBs, the SP and elastic recovery (ER) of the branched SB PMBs were higher by 5–10 °C and 5–10%, while δ was lower by 15–25°. Among the four SB polymers investigated, the properties of the diblock SB PMBs were the lowest. Our study suggests that the branched SB polymer due to higher network density will produce PMBs that will perform better at upper pavement design temperature. This study provides valuable insights that could be highly beneficial for the pavement construction industry.